Genome-Wide Identification of Alternative Splicing in Botrytis cinerea During Infection Stage of Solanum lycopersicum - Ping Lu; Yun Wang; Xiaoli Wang; Jiaqi Wang; Dan Wang; Haojie Shi (Microorganisms)
Alternative splicing plays a crucial role in enhancing the protein diversity of eukaryotic genomes. However, alternative splicing has not been extensively studied in Botrytis cinerea. In this study, we examined the distribution and regulation of alternative splicing in the filamentous plant pathogenic fungus B. cinerea through strand-specific RNA sequencing at various stages of infection of Solanum lycopersicum. During infection (pre-penetration and biotrophic stage), most spliceosome genes had upregulated expression levels, indicating that splicing is altered at this stage. A total of 3308 genes underwent alternative splicing in B. cinerea, resulting in 7466 alternative splicing events, most of which were stage-specific. Transcripts generated through alternative splicing typically exhibit lower expression levels, coding potential, and functional domains, which are more prevalent during the hyphal phase compared to the infestation phase. To conclude, our research offers an extensive analysis of the genome-wide alternative splicing in B. cinerea throughout the infection process, acting as a significant resource for further clarifying the pathogenic mechanisms associated with B. cinerea.